Empowering Communities to Prevent Stunting: A Study in Sitiris-Tiris Village, Tapanuli Tengah Regency, North Sumatra Province - Gaja, Fatma Zuhro; Sahrul, Sahrul (TEMALI : Jurnal Pembangunan Sosial, 2024)
Stunting in children, caused by chronic malnutrition from ages 0-5, negatively impacts physical and psychomotor development as well as their future. This nutritional deficiency often results from a lack of public knowledge about stunting and preventive measures. This study aims to explore community empowerment efforts to prevent stunting in Sitiris-tiris Village, Andam Dewi District, Tapanuli Tengah Regency, North Sumatra Province. The research employs a qualitative method. Data collection involves direct observation at Posyandu Beringin in Sitiris-tiris Village and interviews with 10 informants, including midwives, nutritionists, cadres, and mothers of young children. The findings reveal that community empowerment through two main programsâ€”educational outreach and DASHAT (Healthy Kitchen to Overcome Stunting)â€”successfully reduced the stunting rate in the village. The educational outreach program increased parents’ knowledge about stunting, while DASHAT focused on improving healthy eating patterns as a preventive measure against stunting. The reduction in stunting rates reflects the success of the community empowerment efforts in the village.